Biomass charcoal material loaded with manganese, iron and cobalt oxides as well as preparation method and application of biomass charcoal material

The biomass carbon material loaded with manganese, iron and cobalt oxides is activated, and the problem of low activation efficiency at room temperature in the prior art is solved, and the effect of efficient degradation of organic pollutants in sewage is achieved, and environmentally friendly and low cost is achieved. .

CN119455975APending Publication Date: 2025-02-18UNIV OF SHANGHAI FOR SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411740305.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively activate persulfate under normal temperature conditions, resulting in low degradation efficiency of organic pollutants in sewage, and high energy consumption, serious environmental pollution and difficult implementation.

Method used

The biomass carbon material supported by manganese, iron and cobalt oxides is used as the activation material, and the material is prepared by step-by-step gradient heating pyrolysis and solid-state mixing of metal source, using its ability to catalytically activate the degradation of organic pollutants by persulfate.

Benefits of technology

Efficient activation of persulfate under normal temperature and natural conditions has significantly improved the degradation efficiency of organic pollutants in sewage, avoided secondary pollution, and is low in cost and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455975A_ABST
    Figure CN119455975A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of organic pollutant degradation, in particular to a biomass charcoal material loaded with manganese, iron and cobalt oxides as well as a preparation method and application of the biomass charcoal material. The preparation method comprises the following steps: performing impurity removal, cleaning and drying on the wood chip biochar to obtain pretreated wood chip biochar; the pretreated wood chip biochar is crushed and sieved, and wood chip powder is obtained; placing the wood chip powder in an inert atmosphere, and carrying out stepped gradient heating pyrolysis to obtain pyrolyzed biochar; and performing solid-solid mixing on the pyrolyzed charcoal, an iron source, a manganese source and a cobalt source, and then repeating the previous pyrolysis process to prepare the biomass charcoal material loaded with manganese, iron and cobalt oxides. The manganese, iron and cobalt oxide loaded biomass charcoal material provided by the invention is environment-friendly, meanwhile, heteroatoms are added, so that the conductivity can be improved, reaction active sites are increased, and the degradation efficiency of persulfate on pollutants in sewage can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of organic pollutant degradation, and in particular to a biomass carbon material loaded with manganese, iron and cobalt oxides, and a preparation method and application thereof. Background Art

[0002] Perfluorinated compounds (PFCs) are a class of artificially synthesized chemical products. The bond energy of the CF bond in the molecule is about 485.3 kJ / mol. Therefore, PFCs have high chemical and thermal stability and are widely used. Perfluorooctane sulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) are the two most widely used perfluorinated compounds. People are very likely to be exposed to PFCs in their daily lives. Perfluorinated compounds are persistent organic pollutants with high chemical stability. They are extremely difficult to degrade in the environment and can exist in sewage for a long time. Discarded perfluorinated compounds pose a threat to ecosystems, birds and mammals, and human health.

[0003] Persulfate is currently commonly used to treat organic pollutants in wastewater. Persulfate (PS) is a new type of advanced oxidant, including perxymonosulfate (PMS) and peroxydisulfate (PDS). Theoretically, PS and H2O2 have strong oxidizing properties. PS is based on SO4 - PS is a commonly used oxidant in advanced oxidation processes. Its redox potential is second only to F2 and O3. However, PS is slow to directly oxidize pollutants in water at room temperature. It needs to be activated to generate SO4. - Then degrade organic pollutants. Currently commonly used activation methods include thermal activation, alkali activation and ultraviolet activation.

[0004] However, thermal activation, alkaline activation and ultraviolet activation are difficult to achieve in actual in-situ wastewater treatment. Thermal activation has problems such as high energy consumption and severe thermal pollution in the actual application process. Alkaline activation is carried out at pH>11, usually using sodium hydroxide or potassium hydroxide to adjust the pH value of the solution. Therefore, alkaline activation has problems such as serious environmental pollution, high reagent costs, and the inability to recover homogeneous catalysts. When the turbidity and other pollutants in the water body are rich, the effectiveness of ultraviolet energy absorbed by PS will be sharply reduced, and it is not possible to implement it in the actual application process.

[0005] Transition metal ion activation can be carried out at room temperature and pressure without additional heating or light. However, conventional transition metals can activate PS, and transition metal cations can compete with other organic matter for SO4 - And it is oxidized to a low-valent state.

[0006] Therefore, there is a need for a biochar material that can effectively activate the persulfate system. Summary of the invention

[0007] The first object of the present invention is to provide a biomass carbon material loaded with manganese, iron and cobalt oxides, which can solve the above-mentioned technical problems.

[0008] The second object of the present invention is to provide a method for preparing a biomass carbon material loaded with manganese, iron and cobalt oxides.

[0009] The present invention provides a method for preparing a biomass carbon material loaded with manganese, iron and cobalt oxides, comprising the following steps:

[0010] S1. removing impurities, washing and drying the sawdust biochar to obtain pretreated sawdust biochar;

[0011] S2. crushing and sieving the pretreated sawdust biochar to obtain sawdust powder;

[0012] S3. placing the sawdust powder under an inert atmosphere and performing step-wise gradient pyrolysis to obtain pyrolyzed biochar; preferably, the inert atmosphere is a nitrogen atmosphere;

[0013] S4. The pyrolyzed biochar is solid-mixed with an iron source, a manganese source and a cobalt source, and then the pyrolysis process of step S3 is repeated to prepare a biochar material loaded with manganese, iron and cobalt oxides.

[0014] Preferably, the sawdust source of the sawdust biochar in step S1 is at least one of fir tree chips, tung tree chips, and camphor tree chips.

[0015] Preferably, the specific steps of step S1 are: soaking the sawdust biochar in 5-7% HCl for 24-36 hours to remove impurities, then washing with deionized water until neutral, and drying the washed sawdust at 100-110° C. for 20-26 hours to obtain pretreated sawdust biochar.

[0016] Preferably, the specific steps of step S2 are: crushing the pretreated sawdust biochar with a high-speed crusher, and then passing it through a 100-mesh sieve to obtain sawdust powder;

[0017] Preferably, the specific steps of the step-by-step gradient temperature increase pyrolysis in step S3 include: stage I is heating from room temperature to 110-130°C at 5-10°C / min, and keeping warm for 15-20min; stage II is heating to 170-190°C at 3-5°C / min, and keeping warm for 10-20min; stage III is heating to 500-800°C at 5-10°C / min, and keeping warm for 2-4h.

[0018] Stage I is a preliminary thermal cracking process, which ensures the inherent shape of the raw materials and shapes a better carbon shape; stage II is a slow thermal decomposition process, which is beneficial to improve the porosity and surface properties of the carbonized products, reduce the ash content, and facilitate the subsequent heteroatom loading; stage III is further heated to generate iron oxides, manganese oxides and cobalt oxides that tend to the most stable valence state, and use external energy to form Fe-C, Mn-C and Co-C bonds, and use higher temperatures to distort the crystals between iron oxides, manganese oxides and cobalt oxides. Due to the oxygen-poor atmosphere, the doping of heteroelements and high temperature destroy the crystal symmetry structure, resulting in crystal defects and partial deprivation of oxygen atoms, especially at the interface between metal oxides and carbon. The fluctuation of oxygen atoms here is oxygen defects. Oxygen defects can form bridging hydroxyls with water and transform into hydroxyl radicals to obtain the catalytic sites required for the activation of persulfate.

[0019] Preferably, in step S4, the iron source is Fe(NO3)3·9H2O, the manganese source is manganese nitrate, and the cobalt source is cobalt nitrate.

[0020] Preferably, the mass ratio of biochar to iron source, manganese source and cobalt source in step S4 is (4-8): 1: 1: 1. Transition metal sources with atomic radius similar to that of iron atoms such as nickel, ruthenium and iridium can also be loaded on the biochar material.

[0021] The present invention also provides a biomass carbon material loaded with manganese, iron and cobalt oxides prepared by the above preparation method.

[0022] The present invention provides the use of the above-mentioned biomass carbon material loaded with manganese, iron and cobalt oxides in activating persulfate. The main reaction principle of the biomass carbon material loaded with manganese, iron and cobalt oxides to activate persulfate is that the functional groups such as -OH, -OOH, -COOH, C-OH in the biomass carbon-based material loaded with iron atoms can undergo metal-like catalytic reactions, and the activated persulfate decomposes to produce sulfate radicals, thereby degrading organic pollutants in sewage. The reaction equation is as follows:

[0023] Carbon surface-OOH+S2O8 2- →Carbon surface-OO·+SO4 - +HSO4 - (1);

[0024] C=C=O+HSO5 - →SO4 - +C=CO + +OH - (2);

[0025] C=CO + +HSO5 -→C=C=O+SO5 - +H + (3).

[0026] Introducing metal atoms (Mn, Co, etc.) with similar atomic radius, electronegativity and charge density to iron atoms into biochar materials can obtain biochar-based materials loaded with atoms of similar radius, thereby changing the electron density in local carbon atoms, improving electron mobility, introducing new active centers and accelerating catalytic electron transfer reactions, thereby enhancing the catalytic performance of activated persulfate in degrading organic pollutants in wastewater.

[0027] The present invention also provides an application of biomass carbon materials loaded with manganese, iron and cobalt oxides in the field of degrading organic pollutants in sewage. The specific application steps are as follows: adding biomass carbon materials loaded with manganese, iron and cobalt oxides to a water body containing organic pollutants, adding persulfate after thorough mixing, and releasing SO4 by activating sodium persulfate. - , the effect of efficiently degrading organic pollutants in organic polluted sewage can be achieved. The preferred persulfate is sodium persulfate. It can not only degrade polychlorinated biphenyls, but also other organic pollutants (such as polycyclic aromatic hydrocarbons, organochlorine, petroleum hydrocarbons and other organic substances).

[0028] Beneficial effects:

[0029] The present invention adopts biomass carbon material as the activation material. The material has a wide source, is relatively low in cost, and is easier to promote and apply in practice.

[0030] The biomass carbon material loaded with manganese, iron and cobalt oxides provided by the present invention loads manganese, iron and cobalt oxides, and compared with traditional metal catalytic materials, it will not produce secondary pollution and is environmentally friendly. At the same time, the addition of the above-mentioned heteroatoms can break the network inertia of the carbon-based material, improve the electrical conductivity, increase the reaction active sites, and can significantly improve the degradation efficiency of persulfate for pollutants in sewage. Persulfate can be efficiently activated at normal temperature and natural conditions to repair organic pollution in sewage. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The X-ray diffraction spectrum (XRD) of MnO / Fe3O4 / Co2O3@BC obtained in Example 1 of the present invention;

[0032] Figure 2 a is the scanning electron microscope (SEM) image of wood chip biochar. Figure 2 b is a scanning electron microscope (SEM) image of MnO / Fe3O4 / Co2O3@BC prepared in Example 1;

[0033] Figure 3Electron paramagnetic resonance (EPR) spectra of sawdust biochar and MnO / Fe3O4 / Co2O3@BC obtained in Example 1;

[0034] Figure 4 This is a graph showing the degradation rate of AO7 degraded by sodium persulfate activated by MnO / Fe3O4 / Co2O3@BC obtained in Example 1 of the present invention;

[0035] Figure 5 This is a degradation rate diagram of PFOA degradation by sodium persulfate activated by MnO / Fe3O4 / Co2O3@BC obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0036] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0037] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0038] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Example 1

[0040] A method for preparing a biomass carbon material loaded with manganese, iron and cobalt oxides comprises the following steps:

[0041] S1. The sawdust biochar was soaked in 5% HCl for 24 hours to remove impurities, then washed with deionized water until neutral, and the washed sawdust was dried in a constant temperature forced air drying oven at 105°C for 24 hours to obtain pretreated sawdust biochar; the sawdust source was a mixture of fir tree chips and tung tree chips.

[0042] S2. The pretreated sawdust biochar was crushed by a high-speed crusher and then passed through a 100-mesh sieve to obtain sawdust powder;

[0043] S3. Put sawdust powder into a quartz boat and place it in a tube furnace. After placing it, pass nitrogen for 30 minutes to remove most of the air in the tube to achieve better anaerobic conditions; put the sawdust powder in an inert atmosphere and perform step-by-step gradient temperature increase pyrolysis. The specific steps of the step-by-step gradient temperature increase pyrolysis include: stage I is to increase the temperature from room temperature to 120°C at 5°C / min and keep it warm for 15 minutes; stage II is to increase the temperature to 180°C at 5°C / min and keep it warm for 15 minutes; stage III is to increase the temperature to 700°C at 5°C / min and keep it warm for 2 hours; and obtain pyrolysis biochar;

[0044] S4. The pyrolyzed biochar was solid-solid mixed with Fe(NO3)3·9H2O, manganese nitrate and cobalt nitrate in a mass ratio of 6:1:1:1, and then the pyrolysis process of step S3 was repeated to prepare a biochar material loaded with manganese, iron and cobalt oxides - MnO / Fe3O4 / Co2O3@BC composite material.

[0045] Example 2

[0046] A method for preparing a biomass carbon material loaded with manganese, iron and cobalt oxides comprises the following steps:

[0047] S1. The sawdust biochar was soaked in 7% HCl for 30 hours to remove impurities, then washed with deionized water until neutral, and the washed sawdust was dried in a constant temperature forced air drying oven at 100°C for 26 hours to obtain pretreated sawdust biochar; the sawdust source was a mixture of fir tree sawdust and camphor tree sawdust.

[0048] S2. The pretreated sawdust biochar was crushed by a high-speed crusher and then passed through a 100-mesh sieve to obtain sawdust powder;

[0049] S3. Put sawdust powder into a quartz boat and place it in a tube furnace. After placing it, pass nitrogen for 30 minutes to remove most of the air in the tube to achieve better anaerobic conditions, so that the sawdust powder is in an inert atmosphere and perform step-by-step gradient temperature increase pyrolysis. The specific steps of the step-by-step gradient temperature increase pyrolysis include: stage I is to increase the temperature from room temperature to 130°C at 8°C / min and keep it warm for 20 minutes; stage II is to increase the temperature to 170°C at 3°C / min and keep it warm for 20 minutes; stage III is to increase the temperature to 800°C at 10°C / min and keep it warm for 3 hours; and obtain pyrolysis biochar;

[0050] S4. The pyrolyzed biochar was solid-solid mixed with Fe(NO3)3·9H2O, manganese nitrate and cobalt nitrate in a mass ratio of 4:1:1:1, and then the pyrolysis process of step S3 was repeated to prepare a biochar material loaded with manganese, iron and cobalt oxides - MnO / Fe3O4 / Co2O3@BC composite material.

[0051] Example 3

[0052] A method for preparing a biomass carbon material loaded with manganese, iron and cobalt oxides comprises the following steps:

[0053] S1. The sawdust biochar was soaked in 6% HCl for 36 hours to remove impurities, then washed with deionized water until neutral, and the washed sawdust was dried in a constant temperature forced air drying oven at 110°C for 20 hours to obtain pretreated sawdust biochar; the sawdust source was a mixture of fir tree chips, tung tree chips and camphor tree chips.

[0054] S2. The pretreated sawdust biochar was crushed by a high-speed crusher and then passed through a 100-mesh sieve to obtain sawdust powder;

[0055] S3. Put sawdust powder into a quartz boat and place it in a tube furnace. After placing it, pass nitrogen for 30 minutes to remove most of the air in the tube to achieve better anaerobic conditions, so that the sawdust powder is in an inert atmosphere and perform step-by-step gradient temperature increase pyrolysis. The specific steps of the step-by-step gradient temperature increase pyrolysis include: stage I is to increase the temperature from room temperature to 110°C at 10°C / min and keep it warm for 18 minutes; stage II is to increase the temperature to 170°C at 4°C / min and keep it warm for 18 minutes; stage III is to increase the temperature to 500°C at 8°C / min and keep it warm for 4 hours; and obtain pyrolysis biochar;

[0056] S4. The pyrolyzed biochar was solid-solid mixed with Fe(NO3)3·9H2O, manganese nitrate and cobalt nitrate in a mass ratio of 8:1:1:1, and then the pyrolysis process of step S3 was repeated to prepare a biochar material loaded with manganese, iron and cobalt oxides - MnO / Fe3O4 / Co2O3@BC composite material.

[0057] Structural testing:

[0058] The MnO / Fe3O4 / Co2O3@BC prepared in Example 1 was tested by X-ray diffractometer, and the XRD pattern was as follows: Figure 1 As shown. Figure 1 It can be seen that the modification of the sawdust biochar in Example 1 of the present invention is successful. After doping with iron, manganese and cobalt, the crystal structure of the biochar is changed, and its crystallinity is improved.

[0059] The morphology of the sawdust biochar used in the present invention was observed, and the scanning electron microscope SEM image is as follows: Figure 2 As shown in a, the structure is relatively loose, with more pores and flaky structures; the morphology of MnO / Fe3O4 / Co2O3@BC prepared in Example 1 was observed, and the scanning electron microscope SEM image is as follows Figure 2 As shown in b, the surface of the material is loaded with a large amount of granular matter, and the overall structure is denser, which is beneficial to improving the catalytic performance.

[0060] Solid EPR analysis was performed on the unmodified sawdust biochar (BC) and the MnO / Fe3O4 / Co2O3@BC obtained in Example 1. Figure 3 . Figure 3 The peak at g=2.002 can prove the existence of oxygen atom fluctuation, i.e. oxygen defect, in the product of Example 1. The oxygen defect can form a bridging hydroxyl group with water and transform into a hydroxyl free radical.

[0061] Performance Test:

[0062] The present invention uses MnO / Fe3O4 / Co2O3@BC with different mass ratios of biochar to metal source (iron source, manganese source, cobalt source) to test the adsorption performance of organic pollutants. As the content of metal source in biochar increases, the adsorption amount first increases and then decreases. The addition of metal oxides is beneficial to the decomposition of biochar and increases the adsorption performance, but excessive metal atoms will cause the pores of biochar to be blocked. The optimal mass ratio between biochar and metal source is 6:1:1:1.

[0063] The present invention uses MnO / Fe3O4 / Co2O3@BC at the pyrolysis temperature of stage III to test the adsorption performance of organic pollutants. As the pyrolysis temperature in stage III increases, the decomposition of organic matter in the biochar is promoted, its surface area and pore structure are increased, which is conducive to the increase of adsorption sites. At the same time, as the temperature rises further, the structure of the biochar may be completely destroyed, affecting the adsorption effect. The test shows that the pyrolysis temperature of 700°C is the best preparation condition.

[0064] When the mass ratio of biochar to metal source is 6:1:1:1 when preparing MnO / Fe3O4 / Co2O3@BC, and the pyrolysis temperature in stage III is 700°C, the maximum adsorption capacity of the prepared product in the organic pollutant adsorption performance test is 13.85 mg / g. In summary, Example 1 is the best example.

[0065] Water organic pollutant removal test:

[0066] In this test, the test water body is simulated sewage, and two test water bodies containing organic pollutants acid orange 7 (AO7) and perfluorooctanoic acid (PFOA) are set, wherein the concentrations of AO7 and PFOA are both 50 mg / L. The MnO / Fe3O4 / Co2O3@BC sample is the product prepared in Example 1.

[0067] The test steps are as follows: Use a 250mL conical flask for degradation experiments, add 200mL of test water to the conical flask, add a stirrer to the bottom of the conical flask during the reaction, and stir magnetically to ensure sufficient reaction. Add MnO / Fe3O4 / Co2O3@BC sample to the test water until the concentration of MnO / Fe3O4 / Co2O3@BC in the solution is 0.5g / L, then add sodium persulfate, and use 0.1mol / LNaOH solution and H2SO4 solution to adjust the pH to neutral.

[0068] The concentrations of sodium persulfate in the test water containing AO7 were 3, 9, 15, 21 and 27 mmol / L, respectively, and 2-3 parallel experiments were conducted for each condition. The degradation reaction was carried out at room temperature for 1 hour. Sampling was performed every 10 minutes, and after sampling, it was filtered through a 0.45 μm filter head and tested by UV-visible spectrophotometer to detect the AO7 concentration. The degradation rate of AO7 degraded by sodium persulfate activated by MnO / Fe3O4 / Co2O3@BC is shown in Figure 2. Figure 4 shown.

[0069] Depend on Figure 4 It can be seen that with the increase of sodium persulfate dosage, the removal rate of AO7 has been significantly improved. When the dosage of sodium persulfate is 15mmol / L, the degradation of AO7 reaches the best effect. After 1h of reaction, the removal rate can reach 90%. However, with the continued increase of sodium persulfate dosage, the removal rate of AO7 shows a downward trend. The reason is that with the increase of sodium persulfate concentration, its own quenching reaction makes the generated SO4 ·- The concentration becomes lower.

[0070] The concentrations of sodium persulfate in the test water containing PFOA were 3, 9, 15 and 21 mmol / L, and 2-3 parallel experiments were conducted for each condition. The degradation reaction was carried out in a constant temperature stirring water bath at 25°C for 7 hours. Sampling was carried out at different time intervals, and 0.2 mL of methanol was immediately added to quench the reaction. The concentration of PFOA solution was then determined using an HPLC-MS / MS instrument. The degradation rate of PFOA degraded by sodium persulfate activated by MnO / Fe3O4 / Co2O3@BC is shown in Figure 2. Figure 5 shown.

[0071] Depend on Figure 5 It can be seen that with the increase of sodium persulfate dosage, the removal rate of PFOA has significantly improved. When the PS dosage is 9mmol / L, the system achieves the best effect on the degradation of PFOA. After 1h of reaction, the removal rate can reach 44%. However, with the continued increase of sodium persulfate dosage, the removal rate of PFOA shows a downward trend. The reason may be that with the increase of sodium persulfate concentration, its own quenching reaction makes the generated SO4·- The concentration becomes lower.

[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a biomass carbon material loaded with manganese, iron and cobalt oxides, characterized in that: The following steps are involved: S1. removing impurities, washing and drying the sawdust biochar to obtain pretreated sawdust biochar; S2. crushing and sieving the pretreated sawdust biochar to obtain sawdust powder; S3. placing the sawdust powder under an inert atmosphere and performing step-by-step gradient pyrolysis to obtain pyrolyzed biochar; S4. The pyrolyzed biochar is solid-mixed with an iron source, a manganese source and a cobalt source, and then the pyrolysis process of step S3 is repeated to prepare a biochar material loaded with manganese, iron and cobalt oxides.

2. The method for preparing biomass carbon material loaded with manganese, iron and cobalt oxides according to claim 1, characterized in that: The sawdust source of the sawdust biochar in step S1 is at least one of fir tree sawdust, tung tree sawdust, and camphor tree sawdust.

3. The method for preparing biomass carbon material loaded with manganese, iron and cobalt oxides according to claim 1, characterized in that: The specific steps of step S1 are: soaking the sawdust biochar in 5-7% HCl for 24-36 hours to remove impurities, then washing with deionized water until neutral, and drying the washed sawdust at 100-110° C. for 20-26 hours to obtain pretreated sawdust biochar.

4. The method for preparing biomass carbon material loaded with manganese, iron and cobalt oxides according to claim 1, characterized in that: The specific steps of step S2 are: crushing the pretreated sawdust biochar with a high-speed crusher, and then passing it through a 100-mesh sieve to obtain sawdust powder.

5. The method for preparing biomass carbon material loaded with manganese, iron and cobalt oxides according to claim 1, characterized in that: The specific steps of the step-by-step gradient heating pyrolysis in step S3 include: stage I is heating from room temperature to 110-130°C at 5-10°C / min, and keeping warm for 15-20min; stage II is heating to 170-190°C at 3-5°C / min, and keeping warm for 10-20min; stage III is heating to 500-800°C at 5-10°C / min, and keeping warm for 2-4h.

6. The method for preparing biomass carbon material loaded with manganese, iron and cobalt oxides according to claim 1, characterized in that: In step S4, the iron source is Fe(NO3)3·9H2O, the manganese source is manganese nitrate, and the cobalt source is cobalt nitrate.

7. The method for preparing biomass carbon material loaded with manganese, iron and cobalt oxides according to claim 6, characterized in that: In step S4, the mass ratio of biochar to the iron source, manganese source and cobalt source is (4-8): 1:1:

1.

8. A biomass carbon material loaded with manganese, iron and cobalt oxides prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the biomass carbon material loaded with manganese, iron and cobalt oxides according to claim 8 in activating persulfate.

10. Use of the biomass carbon material loaded with manganese, iron and cobalt oxides as claimed in claim 8 in the field of degradation of organic pollutants in sewage.

Citation Information

Cited By

  • Bio-based metal carbon material, preparation method thereof and application of bio-based metal carbon material in dark fermentation biological hydrogen production

    CN121178167A